Archaeological Gleanings from Killin - Cash, C G (Proceedings of the Society of Antiquaries of Scotland, 1912)
A number of cup-marked rocks are described and illustrated. The account also features standing stones, burial grounds and oddities such as St Filan's curing stones and Fingal's grave which is marked be a standing stone.